Disseminated Histoplasmosis in a Patient with Advanced HIV Disease - Lessons Learnt from Bangladesh (Journal of Health, Population and Nutrition, 2010)
Histoplasmosis is a systemic fungal disease, also known as Darling’s disease, caused by the dimorphic fungusHistoplasma capsulatum. It is usually self-limiting or localized in immunecompetent individuals whereasin patients with acquired immune deficiency syndrome (AIDS), it occurs in the disseminated form in 95%of cases. Although histoplasmosis predominates in the Americas (United States and Latin America, includingBrazil) as an important infection among AIDS patients, it is not common in Bangladesh. In contrast,tuberculosis is extremely common in Bangladesh, with an estimated prevalence of 387 per 100,000 people.Here, a confirmed case of disseminated histoplasmosis is reported in Bangladesh in a known HIV-positivepatient, which was initially suspected to be extrapulmonary tuberculosis.Key words: Case studies; Histoplasma capsulatum; Histoplasmosis; HIV; Tuberculosis; BangladeshDOI: 10.3329/jhpn.v28i3.5561J HEALTH POPUL NUTR 2010 Jun;28(3):305-307